2017
DOI: 10.1152/jn.00721.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal microstimulation and diaphragm activation after cervical spinal cord injury

Abstract: Intraspinal microstimulation (ISMS) using implanted electrodes can evoke locomotor movements after spinal cord injury (SCI) but has not been explored in the context of respiratory motor output. An advantage over epidural and direct muscle stimulation is the potential of ISMS to selectively stimulate components of the spinal respiratory network. The present study tested the hypothesis that medullary respiratory activity could be used to trigger midcervical ISMS and diaphragm motor unit activation in rats with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…The primary therapeutic goal of neural stimulation post-SCI is to activate otherwise silenced/paralyzed circuitry and muscles. When applied under the right conditions the beneficial effects can also persist after termination of treatment (Mercier et al, 2016; Posluszny et al, 2014). Such therapies, summarized in Figure 3, are designed to stimulate neural activity via electrical stimuli applied to the periphery (functional electrical stimulation (A)), spinal cord (epidural stimulation (B) or intraspinal microstimulation (C), and transcranial magnetic stimulation (D)) or supraspinal regions (transcranial magnetic stimulation and deep brain stimulation), or via physical stimuli (locomotor training (F) and respiratory rehabilitation (E)).…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…The primary therapeutic goal of neural stimulation post-SCI is to activate otherwise silenced/paralyzed circuitry and muscles. When applied under the right conditions the beneficial effects can also persist after termination of treatment (Mercier et al, 2016; Posluszny et al, 2014). Such therapies, summarized in Figure 3, are designed to stimulate neural activity via electrical stimuli applied to the periphery (functional electrical stimulation (A)), spinal cord (epidural stimulation (B) or intraspinal microstimulation (C), and transcranial magnetic stimulation (D)) or supraspinal regions (transcranial magnetic stimulation and deep brain stimulation), or via physical stimuli (locomotor training (F) and respiratory rehabilitation (E)).…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
“…In recent years, intraspinal microstimulation (see Figure 3C) has been shown to effectively promote some recovery of both lower (Bamford and Mushahwar, 2011; Bamford et al, 2011; Bamford et al, 2010) and upper (Kasten et al, 2013; Moritz et al, 2007; Sunshine et al, 2013) extremities post-SCI. Intraspinal microstimulation has now also been used to activate respiratory circuitry caudal to SCI (Mercier et al, 2016). Stimulating the C4 ventral grey matter via a single tungsten microwire (100Hz), Mercier et al (2016) demonstrated restoration of activity to the paralyzed hemidiaphragm acutely following C2Hx, that persisted even once stimulation ceased.…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency spinal cord stimulation has also successfully been used to restore cough in patients with SCI (DiMarco et al, 2014). Direct intraspinal stimulation has also been used in rats to activate phrenic motor neurons for breathing, likely via propriospinal neurons (Mercier et al, 2017). However, the neural substrates upon which the spinal cord stimulation acts are not currently clear.…”
Section: Propriospinal Neurons Modulate Respiratory Motor Output Follmentioning
confidence: 99%
“…Previous studies have suggested technology that can be used to synchronize artificial ventilation with intrinsic respiratory drive or to replicate its function. These methods include development of a controllable stimulator with an update frequency higher than the stimulation frequency and a real-time processing controller (Castelli et al, 2017), implementation of a bio-inspired spiking neural network model that follows intrinsic respiratory rate (Zbrzeski et al, 2016), predictive algorithms using body temperature and heart rate (Kimura et al, 1992), and breath-triggering through the use of genioglossus muscle activity (Mercier et al, 2017). However, these approaches have not yet been sufficiently developed or investigated.…”
Section: Controller Provided Autonomous and Individualized Ventilatormentioning
confidence: 99%